Growth Management Revisited: A Reassessment of its Efficacy, Price Effects and Impacts on Metropolitan Growth Patterns - John D. Landis; Lan Deng; Michael Reilly (University of California, Institute of Urban and Regional Development (IURD), 2002)
Once a favorite topic of urban economists and land use planners, local growth control and growth management (LGC&M) programs have become passé, swept off the front pages of professional and academic journals alike by more current topics like smart growth and sprawl. Smart growth, with its emphasis on bottom-up, locally appropriate, and proactive planning is in, while growth management, with its reputation for top-down planning and blunt regulation is out. In reality, of course, smart growth is simply the newest adaptation of growth management (which is itself an adaptation of growth control), albeit with a more incentive- and project-based focus. Likewise, controlling sprawl has long been growth management?s principal spatial objective. Thus, how well past and ongoing efforts at growth management programs have succeeded in meeting their objectives should be of prime concern to today?s advocates of smart growth. Outside the immediate visage of regional policy analysts and smart growth boosters, the LGC&M movement remains extremely active, especially at the ballot box and especially in California (Baldassare 2001). A 15-year analysis by Fulton et al. (2000) shows LGC&M activity to be strongly correlated with state and regional growth rates?rising during expansionary periods such as the late-1980s and late-1990s, and falling during slowdown periods such as the early-1990s. Although exact numbers are hard to come by, we estimate that about three-quarters of California cities and two-thirds of California counties have adopted some form of LGC&M program since 1980.
Keywords: 330; Kommunalplanung; Stadtwachstum; Wohnungsbaupolitik; Kalifornien